Effect of 0.01% Atropine on Accommodation in Myopic Teenagers - Huixia Li; Liying Zhang; Hong Tian; Song Zhang; Xueyan Zhang; Han Zhang; Yujing Chen; Wenping Qi; Xiaoying Wu; Hongmei Jiang; Hailong Yang; Yajun Yang; et al. (Frontiers Media S.A., 2022)
Purpose: The purpose of the study is to evaluate the effects of 0.01% atropine eye drops on accommodative system parameters among teenagers with low myopia.Methods: Ninety-five myopic teenagers [39 boys (8.69 ± 2.473) and 56 girls (8.54 ± 2.054) aged 5-17 years] with no history of eye disease were enrolled. Biometric and accommodative system parameters were evaluated before and at 1 week, 1 month, 3 months, and 6 months of 0.01% atropine eye drop instillation.Results: Participants without accommodative demand at 6 months demonstrated insignificant changes after the atropine instillation (all p > 0.05). Nevertheless, there were significant differences in accommodative sensitivity, accommodative amplitude, accommodative responsiveness, and negative relative accommodation (NRA) at 3 months compared with baseline after atropine instillation (all p < 0.05). Except spherical equivalent refraction, cornea thickness, intraocular pressure, and axial length were stable after the 0.01% atropine instillation (all p > 0.05).Conclusion: Morphologically, current measurements suggested that 0.01% atropine had favorable reduction of accommodation for childhood low myopia over a half-year period.